Preparation method of porous carbon coated modified negative electrode material
Through the preparation method of the modified negative electrode material of porous carbon coated, the problems of uneven coating, pore structure compression and insufficient surface polarity of the negative electrode material of lithium-ion battery are solved, and the efficient stability of the battery in high-rate charging and discharging and long-term cycles are achieved.
Patent Information
- Application Number
- CN202510340992.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-21
- Publication Date
- 2025-04-18
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
In the prior art, the uneven coating of the negative electrode material of lithium-ion battery, the compression of the pore structure and insufficient surface polarity lead to a degradation of the battery's performance in high-rate charging and discharging, long-term cycles and high-temperature environments.
The preparation method of porous carbon coated modified negative electrode material is adopted to optimize the pore structure, surface polarity and mechanical stability of the material through low-temperature pre-carbonization, etching and forming a graded pore structure, high-temperature carbonization and structural reconstruction, porosity control, protective coating deposition and final heat treatment.
It significantly improves the cycle stability, mechanical strength and electrical conductivity of the negative electrode material, extends the service life of the battery, and solves the problems of high-rate charging and discharging and capacity attenuation during long-term cycles.
Smart Images

Figure CN119841305A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of optimization of negative electrode materials for lithium ion batteries, and in particular to a method for preparing a porous carbon-coated modified negative electrode material. Background Art
[0002] With the popularity of electronic devices and the increasing demand for portable power sources, lithium-ion batteries have become an indispensable energy supply method in modern society. From smartphones to electric vehicles, lithium-ion batteries are used in almost every field. In order to improve the performance of batteries, especially the stability in high energy density and long-term use, the development of high-performance negative electrode materials has become one of the keys to improving the overall efficiency of batteries. To this end, more and more research is devoted to optimizing the structure, surface properties and electrochemical characteristics of negative electrode materials, so that the battery can maintain stable and efficient performance in high-rate charge and discharge, high-temperature environment and long-term cycle use.
[0003] In the prior art, the optimization of negative electrode materials mainly focuses on improving the pore structure and conductivity of the materials. For example, through carbonization or sintering technology, many studies have successfully improved the conductivity of negative electrode materials, so that they exhibit good electrochemical performance under conventional charging and discharging conditions. In addition, coating technology is also widely used to improve the chemical stability of materials, avoid direct contact between electrolyte and negative electrode materials, and thus reduce the occurrence of side reactions. These prior arts have achieved certain results in improving the stability, conductivity and electrochemical properties of negative electrode materials, especially in some conventional applications, they can provide relatively satisfactory performance.
[0004] However, the existing technology still has some shortcomings; first, although the stability of the material can be improved by coating technology, it is often difficult to make the coating uniform and consistent in thickness, which affects the high-rate discharge performance of the material; second, the high-temperature sintering in the existing technology often leads to compression of the pore structure, thereby affecting the specific capacity of the material and the cycle stability during long-term use; more importantly, the existing technology has not effectively solved the problem of insufficient surface polarity of the negative electrode material, resulting in poor compatibility between the electrolyte and the electrode, which in turn exacerbates the attenuation of battery performance during long-term use. Summary of the invention
[0005] In view of the deficiencies of the prior art, the present invention provides a method for preparing a porous carbon-coated modified negative electrode material, which solves the problems of uneven coating, compressed pore structure and insufficient surface polarity of the negative electrode material in the prior art.
[0006] To achieve the above objectives, the present invention is implemented by the following technical scheme: A method for preparing a porous carbon-coated modified negative electrode material, comprising the following steps: S1. Low-temperature pre-carbonization: an organic framework structure is formed under the action of carbon source, nitrogen dopant, structure regulator and sacrificial template; S2. Etching to form a hierarchical pore structure: using a chemical etching method to remove the sacrificial template to form a carbon material skeleton with a specific pore distribution; S3, high temperature carbonization and structural reconstruction: high temperature carbonization is carried out in an inert atmosphere to crystallize the carbon material, and the pore distribution is optimized by atmosphere regulation; S4. Porosity control method of negative electrode materials: optimize pore distribution by controlling etching time and atmosphere to ensure the porosity and ion diffusion capacity of the material; S5, depositing a protective coating to form an interfacial stabilization layer on the surface of the carbon material to improve the stability and conductivity of the negative electrode material; S6. Final heat treatment of negative electrode materials: Optimize the surface polarity and perform low-temperature sintering of negative electrode materials to improve mechanical stability and electrolyte wettability.
[0007] Preferably, the low-temperature pre-carbonization comprises: Phenolic resin is used as a carbon source, guanine is used as a nitrogen dopant, CTAB is used as a structure regulator, and SiO2 is added as a sacrificial template, and the mixture is mixed and stirred in deionized water for 2.5-4.0 hours at a stirring speed of 400-600 rpm; The mixed solution is subjected to a hydrothermal reaction at a temperature of 160-180° C. for a duration of 10-14 h to form a gel precursor; Low temperature drying of the obtained precursor at 80-100°C for 12 h to remove the solvent; The initial carbonization is carried out at 500-600°C, the atmosphere is Ar / N2 mixed gas, and the carbonization time is 1.5-3.0h.
[0008] Preferably, the etching to form a graded pore structure comprises: The low-temperature carbonized sample was etched using a 40-50% HF solution for 2.0-3.5 h. Etching was performed under the assistance of 40kHz, 100W ultrasound to improve the uniformity of the pore structure; After washing with deionized water until neutral, vacuum drying is performed at 80-100°C for 10-14h.
[0009] Preferably, the high temperature carbonization and structural reconstruction comprises: The etched sample is heated to 800-900°C at 5-10°C / min in an inert atmosphere and kept at this temperature for 1.5-3.0h; During the cooling process, a CO2 / N2 atmosphere was introduced with a gas volume ratio of 3:7 to control the pore structure; After cooling, XRD analysis is performed to ensure that the crystallinity of the carbon material meets the expected requirements.
[0010] Preferably, the method for controlling the porosity of the negative electrode material comprises: By controlling the etching time, the porosity of the obtained material is within the range of 55-65%; The fractal Brownian motion model is used to optimize the pore size distribution so that the Hurst index is between 0.7 and 0.85; The Levy flight diffusion model was used to optimize the mesopore ratio and control the Levy index α at 1.5.
[0011] Preferably, the protective coating deposition comprises: TiO2 was deposited by sol-gel method, with TiCl4 as precursor, the volume ratio of TiCl4 to ethanol was 1:50, and the stirring time was 2h; The negative electrode material is suspended in a TiO2 solution and subjected to ultrasound-assisted deposition at an ultrasound frequency of 20kHz, a power of 150W, and a reaction time of 4-6h; After being taken out, it is dried and calcined at 400°C for 30-60 minutes.
[0012] Preferably, the thickness of the TiO2 protective layer is controlled at 3-8 nm to ensure the balance of electron-ion transmission.
[0013] Preferably, the protective coating deposition further comprises: MoS2 was deposited by CVD method, with MoO3 and sulfur powder as precursors, placed in different temperature zones, where the temperature of MoO3 was 750℃ and the temperature of S was 200℃; Use Ar / N2 mixed atmosphere, volume ratio 3:7, reaction time 20-40min; After the reaction, it is cooled naturally to form a stable MoS2 coating layer.
[0014] Preferably, the final heat treatment of the negative electrode material comprises: After high-temperature carbonization, cold plasma treatment is used to optimize the polar groups on the surface of the material and improve its wettability with the electrolyte; Low-temperature sintering technology is used, with a temperature range of 500-700°C and a sintering time controlled at 20-60 minutes to enhance the mechanical stability of the electrode.
[0015] Preferably, the thickness of the obtained porous carbon-coated modified negative electrode material is controlled at 5-20 μm, and by adjusting the thickness of the protective layer, its specific capacity is ensured to be in the range of 1000-1200 mAh / g.
[0016] The present invention provides a method for preparing a porous carbon-coated modified negative electrode material, which has the following beneficial effects: 1. The present invention successfully optimizes the surface polarity of the negative electrode material and improves the interfacial affinity with the electrolyte through the cold plasma treatment technical solution. This treatment method significantly reduces the side reactions between the electrolyte and the negative electrode material and effectively improves the cycle stability of the battery. Compared with traditional technologies, the present invention can maintain the long-term stability of the battery under high-rate charge and discharge conditions, solving the capacity attenuation problem caused by interface incompatibility in the prior art.
[0017] 2. Through low-temperature sintering technology, the present invention improves the mechanical strength and conductivity of the negative electrode material. The sintering process effectively eliminates internal stress, strengthens the material structure, and ensures the stability of the battery in high temperature and long-term use. Compared with materials that have not been sintered, the present invention provides stronger compressive resistance and lower internal resistance, significantly improving the high-rate discharge performance of the battery.
[0018] 3. The present invention combines cold plasma treatment with low-temperature sintering to optimize the electrochemical performance of the negative electrode material. This comprehensive treatment scheme not only improves the conductivity, but also enhances the stability of the material. In high-rate discharge and long-term cycling, the battery exhibits higher efficiency and lower capacity attenuation. Compared with the existing technical solutions, the present invention solves the problem of battery performance degradation under high-rate charge and discharge.
[0019] 4. The present invention improves the wettability of the negative electrode material and the electrolyte through an innovative surface polarity enhancement method. This innovative technical measure greatly improves the distribution of the electrolyte on the electrode surface and ensures the efficient conductivity of the material during the charge and discharge process. Compared with the traditional method, the present invention enables the battery to maintain a low internal resistance after multiple cycles, significantly extending the battery life. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 The present invention is a flow chart of the method. DETAILED DESCRIPTION
[0021] The following will be combined with the drawings in the specification of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0022] Please refer to the attached Figure 1 The present invention provides a method for preparing a porous carbon-coated modified negative electrode material, comprising the following steps: S1. Low-temperature pre-carbonization: an organic framework structure is formed under the action of carbon source, nitrogen dopant, structure regulator and sacrificial template; The function of step S1 is to form an organic framework structure by combining carbon source, nitrogen dopant, structure regulator and sacrificial template under appropriate temperature and conditions through low-temperature pre-carbonization. Low-temperature pre-carbonization not only provides a stable foundation for subsequent steps, but also effectively controls the pore structure of the carbon skeleton and the degree of nitrogen doping, and is a key link in the entire process.
[0023] First, in this embodiment, phenolic resin is selected as the main carbon source, guanine is used as a nitrogen dopant, CTAB is used as a structural regulator, and silicon dioxide (SiO2) is used as a sacrificial template. The ratio of phenolic resin to guanine is between 2.5 and 3.5 parts of phenolic resin and 0.5 to 1.2 parts of guanine to ensure that the nitrogen doping level in the reaction is moderate and the resin can be effectively converted into a carbon material. The amount of CTAB used is generally 0.2 to 0.6 parts, which is used to regulate the pore morphology of the carbon material. The proportion of silicon dioxide (SiO2) as a template material is set to 1.0 to 2.0 parts, the purpose of which is to form a carbon skeleton with a certain pore structure by a template method.
[0024] After mixing all the above raw materials, add them into deionized water and stir. The stirring time is usually controlled at 2.5 to 4 hours, and the stirring speed is 400 to 600rpm. During the stirring process, the phenolic resin gradually dissolves, and guanine reacts chemically with the resin to form a nitrogen-containing organic framework structure. The addition of CTAB ensures that the material forms a more uniform pore structure and provides assistance for the formation of a hierarchical pore structure in the subsequent process. SiO2 is used as a sacrificial template, and its main function is to be removed in the subsequent etching process to provide support for the final porous carbon skeleton.
[0025] Subsequently, the mixed solution is placed in a hydrothermal reactor for a hydrothermal reaction. The temperature of the hydrothermal reaction is set to 160°C to 180°C, and the reaction time is controlled to 10 to 14 hours. Under this condition, the phenolic resin and guanine undergo a cross-linking reaction to form a nitrogen-doped organic framework structure. During the reaction, the nitrogen atoms of guanine enter the resin skeleton, increasing the conductivity and electrochemical properties of the final material. By controlling the temperature and reaction time, the concentration of nitrogen doping can be precisely adjusted to optimize the performance of the material.
[0026] After the hydrothermal reaction is completed, the resulting gel precursor needs to be dried at low temperature. Usually, it is dried at 80°C to 100°C for 12 hours to remove the solvent and unreacted organic matter. The purpose of low-temperature drying is to prevent structural damage during high-temperature drying while maintaining the structural stability of the precursor.
[0027] Finally, the dried precursor is subjected to preliminary carbonization. The preliminary carbonization is carried out at a temperature of 500°C to 600°C for 1.5 hours to 3 hours. During this process, a mixed gas of argon and nitrogen is used as the atmosphere to ensure an inert environment for the reaction. At this temperature, the organic components gradually decompose to form a preliminary carbon skeleton. At this time, the nitrogen-doped components are still retained in the carbon skeleton, and nitrogen-doped carbon materials begin to form.
[0028] During the implementation of low-temperature pre-carbonization, phenolic resin is used as a carbon source and guanine is used as a nitrogen source. The selection of both is very critical. Phenolic resin can be cross-linked at low temperatures to form a stable carbon framework, while the nitrogen-doped properties of guanine can introduce nitrogen into the material to improve the conductivity and electrochemical properties of the negative electrode material. As an option, CTAB, as a surfactant, can effectively control the morphology of the pores, so that the final carbon material has a better pore distribution and specific surface area.
[0029] In addition, the use of silicon dioxide (SiO2) as a sacrificial template is a major innovation of the present invention. SiO2 can not only stabilize the hydrothermal reaction, but also be removed by subsequent etching to form a hierarchical pore structure, thereby improving the electrolyte wettability and ion diffusivity of the material. Different from the traditional template method, mild low-temperature conditions are used in the present invention to form the precursor, which helps to retain more organic components and reduce material loss during the carbonization process.
[0030] Specifically, through this low-temperature pre-carbonization process, the organic matter in the precursor is gradually converted into an intermediate with a stable carbon skeleton and forms a certain nitrogen-doped structure. The introduction of these nitrogen-doped components helps to optimize the electrochemical performance of the negative electrode material, especially the performance during high-rate discharge and long cycle processes.
[0031] Through the implementation of the low-temperature pre-carbonization step, the final precursor has a good nitrogen-doped layer and a uniform pore structure, which provides an ideal foundation for the subsequent etching, carbonization and coating deposition steps. The porosity and nitrogen doping degree of the material are precisely controlled, which is crucial to improving the specific capacity, cycle stability and high-rate performance of the negative electrode material. Specifically, by regulating the reaction temperature, time and reaction atmosphere, the structural optimization of the carbon skeleton can be achieved, ensuring the high conductivity and excellent ion diffusion performance of the negative electrode material.
[0032] Through this step, not only can the porosity of the material be well preserved, but also the stability of the nitrogen-doped layer can be enhanced, thereby improving the cycle life and overall electrochemical performance of the battery's negative electrode material. In addition, this step also ensures that the silica template can be completely removed in the subsequent etching process, thereby obtaining a more ideal pore structure, which is crucial to the high efficiency performance of the battery.
[0033] S2. Etching to form a hierarchical pore structure: using a chemical etching method to remove the sacrificial template to form a carbon material skeleton with a specific pore distribution; S2 is etching to form a hierarchical pore structure. Through etching, not only can the sacrificial template be removed, but the pore structure of the material can also be precisely controlled by chemical etching methods, so that the carbon material forms a multi-level pore structure. This process is very critical, and it directly affects the electrochemical properties of the final negative electrode material, especially parameters such as specific surface area, pore distribution and ion diffusion capacity.
[0034] In this step, the template material is removed by chemical etching while maintaining the stability of the carbon material skeleton, and pores with a hierarchical pore structure are formed in the skeleton. This hierarchical pore structure can provide a larger specific surface area, providing more reaction interfaces and paths for efficient charging and discharging of lithium-ion batteries, thereby greatly improving the performance of the battery.
[0035] In this embodiment, the sample after low-temperature carbonization is first chemically etched using a hydrogen fluoride (HF) solution, the concentration of which is generally set to 40% to 50%. This concentration of HF solution is highly corrosive and can effectively remove the silicon dioxide (SiO2) template without damaging the skeleton structure of the carbon material.
[0036] The choice of etching time is crucial to the formation of pore structure. In general, the etching time is controlled between 2 hours and 3.5 hours. If the time is too short, the template may not be completely removed, resulting in an incomplete pore structure; if the time is too long, the carbon skeleton may become unstable. Therefore, precise control of etching time is a key factor in obtaining an ideal pore distribution.
[0037] As an option, the present invention adopts ultrasonic assisted etching technology, which can enhance the permeability of the etching solution and accelerate the etching process through the vibration effect of high-frequency ultrasound, thereby improving the uniformity of the pores. Specifically, the frequency of the ultrasound is set to 40kHz and the power is 100W. At this time, the ultrasound can make the etching solution evenly penetrate into each pore of the carbon material, effectively avoiding the problem of local excessive corrosion and ensuring the uniformity of the pores.
[0038] After etching, the sample is thoroughly cleaned with deionized water to ensure that the residual hydrogen fluoride solution is completely removed and washed to neutrality. The use of deionized water can effectively avoid the influence of residual acidic substances on subsequent processing and ensure the purity of the material.
[0039] Subsequently, the sample is placed in a vacuum drying oven at 80°C to 100°C for 10 to 14 hours of vacuum drying. The purpose of this step is to remove moisture and ensure the stability of the pore structure of the material. Because the evaporation rate of water is faster in a vacuum environment, it can effectively prevent the pore structure from changing or collapsing, ensuring its stability.
[0040] In this step, the use of hydrogen fluoride solution is one of the key technologies. HF solution is highly corrosive and can selectively remove the silicon dioxide (SiO2) template, leaving the skeleton of the carbon material. By precisely controlling the concentration of the HF solution and the etching time, the size, morphology and distribution of the pores can be controlled. This optimization of the pore structure can not only significantly increase the specific surface area of the material, but also increase the diffusion rate of lithium ions in the negative electrode material, thereby improving the performance of the battery.
[0041] In some embodiments, the use of ultrasonic assisted etching technology can further optimize the uniformity of pores. The high-frequency vibration of ultrasound can enhance the fluidity and permeability of the liquid, and help the etching liquid to act evenly on the surface of the material and inside the pores, thereby avoiding the uneven pore phenomenon caused by uneven liquid distribution in traditional methods. Especially when processing materials with complex morphology, ultrasonic assisted etching can ensure a more uniform etching effect.
[0042] Optimization of etching time and HF solution concentration is also key to this step. Shorter etching time and lower solution concentration can form smaller pores, while longer etching time and higher concentration HF solution can form larger pores. According to different needs, the porosity and pore size distribution of the material can be controlled by adjusting these parameters. As an option, the pore structure that is more suitable for battery negative electrode materials usually has a graded pore size, from micropores to mesopores to macropores, to form an ideal porous structure.
[0043] Through this etching step, a hierarchical pore structure was successfully introduced into the carbon skeleton. This hierarchical pore structure not only increases the specific surface area of the material, but also optimizes the pore size distribution, which helps to improve the ion diffusion capacity of the battery material. The advantage of the hierarchical pore structure is that it can provide more transmission paths for lithium ions, thereby reducing the resistance to ion diffusion and improving the rate performance and cycle life of the battery.
[0044] In a possible implementation, by adjusting the pore distribution and porosity, the resulting porous carbon material can have a large specific surface area without affecting the mechanical strength of the material due to excessive pores. In some embodiments, the porosity of the resulting material is controlled between 55% and 65%, which can ensure that the material has good performance during the charge and discharge process.
[0045] In addition, by optimizing the etching conditions, the uniformity of the pores can be further improved, making the pore size distribution more extensive and uniform. This hierarchical pore structure can not only effectively improve the specific capacity of the battery, but also improve the cycle stability of the battery. Since the pores are distributed over a wide range, from micropores to macropores, the resistance to ion diffusion is reduced during long-term use of the battery, effectively extending the battery life.
[0046] By precisely controlling the etching time, etching solution concentration, and using ultrasonic assistance, the size and distribution of the pores can be effectively controlled, thereby improving the electrochemical properties of the negative electrode material.
[0047] S3, high temperature carbonization and structural reconstruction: high temperature carbonization is carried out in an inert atmosphere to crystallize the carbon material, and the pore distribution is optimized by atmosphere regulation; The main purpose of S3 is to further optimize the crystallinity and conductivity of carbon materials through high temperature treatment, and optimize the pore structure through atmosphere regulation, ultimately improving the electrochemical performance of negative electrode materials. Through this step, the structure of carbon materials will be stabilized, so that negative electrode materials can show excellent performance in high rate discharge and long cycle use.
[0048] In this embodiment, the etched carbon material is first subjected to high-temperature carbonization. The temperature of high-temperature carbonization is set to 800°C to 900°C, and the heating rate is controlled at 5°C to 10°C per minute. This temperature range is to ensure that the carbon material can crystallize and improve its conductivity, while avoiding material ablation or pore collapse caused by excessive temperature. During the temperature increase process, the organic components in the carbon material will further decompose to form a more ordered carbon structure, thereby improving the conductivity, thermal stability and mechanical properties of the material.
[0049] In some embodiments, the setting of the heating rate is very important. Too fast heating may cause thermal stress, resulting in the destruction of the carbon skeleton or the shrinkage of pores. To avoid this, the heating rate during the carbonization process should be relatively slow, usually controlled at 5°C to 10°C per minute, to ensure uniform temperature distribution and avoid local overheating and structural damage.
[0050] During the carbonization process, the choice of atmosphere is also crucial. An inert atmosphere, such as nitrogen (N2) or argon (Ar), is used to avoid oxidation caused by the reaction of carbon materials with oxygen. Under an inert atmosphere, the carbon skeleton will be more stable and avoid the introduction of excessive oxygen, thereby ensuring the electrochemical performance and stability of the material.
[0051] As an option, in order to further optimize the pore structure during the carbonization process, a mixture of carbon dioxide and nitrogen (gas volume ratio of 3:7) was used. Carbon dioxide not only has an inert effect, but also helps to adjust the pore structure through its slight reaction with the carbon material, reducing excessive pore shrinkage and keeping it within the optimal range. This atmosphere regulation effect not only promotes the stabilization of the carbon material, but also effectively optimizes the pore morphology.
[0052] Specifically, the addition of carbon dioxide helps alleviate the problem of excessive high-temperature ablation of the material during the carbonization process, thereby controlling the size and distribution of pores and maintaining the pore stability of the material. In addition, nitrogen helps to further optimize the surface structure of the carbon material and improve its electrical conductivity and ion diffusion properties.
[0053] During the carbonization heat preservation process, the duration is usually set to 1.5 hours to 3 hours. During this period, the carbon material will complete the optimization of the lattice structure at high temperature and gradually remove the residual organic components to form a high-quality nitrogen-doped carbon skeleton. Precise control of this process is very important. Too long carbonization time may cause excessive shrinkage of the carbon material, while too short a time may result in an imperfect structure of the material.
[0054] In one possible implementation, the cooling process also requires special attention. After carbonization, in order to avoid uneven accumulation of thermal stress inside the material, the cooling process adopts natural cooling or slow cooling to ensure that the material will not crack or structurally damage during the cooling process. This cooling method helps to further improve the structural stability of the material and avoid brittleness caused by rapid cooling.
[0055] After the carbonized material is cooled, X-ray diffraction (XRD) analysis is usually used to verify the crystallinity of the carbon material. XRD test results usually show obvious graphitization characteristics, indicating that the carbon material has been successfully crystallized and has good conductivity. In some embodiments, by adjusting the temperature and atmosphere during the carbonization process, the crystallinity and pore structure of the carbon skeleton can be precisely controlled to optimize the electrochemical performance of the negative electrode material.
[0056] In this step, the control of temperature, time and atmosphere is the key factor that determines the performance of the final carbon material. Temperature control is the most basic, and the appropriate carbonization temperature can ensure the crystallization of the carbon material and improve its conductivity. For the negative electrode material in the present invention, the temperature range of 800°C to 900°C is the best choice, which not only helps to maintain the stability of the carbon skeleton, but also ensures the uniform distribution of the nitrogen doping components.
[0057] In terms of atmosphere control, the addition of a mixed atmosphere of carbon dioxide and nitrogen further optimizes the pore structure during the carbonization process, making the pore distribution more uniform and avoiding excessive pore shrinkage during the carbonization process. Compared with the traditional inert atmosphere carbonization method, this atmosphere control strategy provides a more optimized pore structure and effectively enhances the ion diffusion capacity of the material.
[0058] In addition, in XRD analysis, the verification of crystallinity is one of the important indicators of carbonization effect. The intensity of the graphitization peak is closely related to the increase in temperature during the carbonization process. In some embodiments, the strong graphitization characteristic peak in the XRD spectrum indicates that the material has achieved ideal crystallization after high-temperature carbonization, further enhancing its electrochemical performance and stability.
[0059] Through the precise control of high-temperature carbonization and atmosphere regulation, the final carbon material exhibits excellent electrochemical properties. First, the crystallinity of the carbon skeleton has been significantly improved, which enhances the conductivity of the material. The ordered structure formed in the carbon material allows electrons to be transferred more smoothly, reducing the internal resistance of the battery and improving the charging and discharging efficiency.
[0060] Secondly, the optimization of the pore structure effectively improves the specific surface area and ion diffusion capacity of the material. The introduction of the hierarchical pore structure provides sufficient space for the rapid insertion and extraction of lithium ions, thereby improving the rate performance and cycle life of the battery. Materials with high specific surface area can provide more electrochemical reaction interfaces and enhance the capacity of the battery.
[0061] In some embodiments, by optimizing the carbonization conditions, the final material not only has a higher specific surface area, but also can maintain a better pore structure, so that the material can still maintain good performance during high-rate charge and discharge.
[0062] Through the implementation of high-temperature carbonization and structural reconstruction steps, the obtained carbon material not only improves crystallinity and enhances conductivity, but also optimizes the pore structure, so that the negative electrode material exhibits excellent electrochemical performance in battery applications. This process ensures the effective application of porous carbon materials in negative electrode materials, especially in high-rate discharge and long-cycle processes.
[0063] S4. Porosity control method of negative electrode materials: optimize pore distribution by controlling etching time and atmosphere to ensure the porosity and ion diffusion capacity of the material; The main goal of S4 is to further optimize the electrochemical performance of materials by precisely controlling porosity, especially in terms of ion diffusion capacity, specific capacity and cycle stability. By finely controlling the size, morphology and distribution of pores, the battery performance of negative electrode materials can be significantly enhanced, especially the stability in high-rate discharge and long-cycle use.
[0064] In this embodiment, porosity control is achieved by optimizing the etching time and precisely controlling the atmosphere composition. Although a pore structure has been initially formed in step S2, in order to further improve battery performance, especially to increase the specific surface area and ion diffusion rate of the material, it is still necessary to finely control the porosity. Controlling the etching time is the first step in optimizing the porosity.
[0065] In general, in order to obtain an ideal porosity range, the etching time is usually set between 2 hours and 3 hours. Within this time range, the material can retain sufficient pores to provide a good ion diffusion path while avoiding a decrease in mechanical strength due to excessive pore size. In some embodiments, excessively long etching time can lead to excessive enlargement of the pores, thereby affecting the stability and cycle performance of the material, so it is necessary to carefully select the appropriate etching time.
[0066] As an option, the optimization of etching time does not rely solely on a single time parameter, but can also be combined with different atmosphere controls to further improve porosity. By introducing atmosphere control, especially using different gas mixtures to accurately adjust the distribution and size of the pore structure. In this embodiment, the fractal Brownian motion (FBM) model and the Levy flight diffusion model were used to optimize the pore distribution. These models not only help to adjust the size of the pores, but also optimize the morphology of the pores, thereby improving the performance of the negative electrode material.
[0067] Specifically, when using the FBM model to control pore distribution, the uniformity of pores is optimized by adjusting the Hurst index (H). Generally, the range of the Hurst index is set between 0.7 and 0.85. The pore distribution within this range is relatively uniform, which can improve the specific surface area and mechanical strength of the material. At the same time, the FBM model can help form a reasonable pore size distribution, which can not only ensure the high specific surface area of the material, but also avoid the instability of the pore structure caused by excessive pore expansion.
[0068] In one possible implementation, by controlling the Levy index (α) in the Levy flight diffusion model, the mesopore ratio can be optimized to be within the ideal range of 1.5. The Levy index is closely related to the diffusion characteristics of the material pores. A lower Levy index usually means better diffusion of the pore distribution, which helps to improve the ion conductivity of the battery, thereby improving the charge and discharge efficiency and rate performance.
[0069] In order to optimize the porosity and pore distribution, the control of atmosphere is another key factor in this step. By adjusting the atmosphere during the etching process, the pore morphology can be effectively optimized and the collapse of the pore structure can be avoided while controlling the porosity. In this embodiment, the stability of the pores is improved by using a protective atmosphere of a mixed gas of carbon dioxide (CO2) and nitrogen (N2).
[0070] The introduction of carbon dioxide helps reduce excessive shrinkage of pores during carbonization, and also helps adjust the shape of pores to make them more suitable for the use of negative electrode materials. The presence of carbon dioxide can reduce the ablation of carbon materials in the pores, ensuring the pore stability and mechanical strength of the material.
[0071] As an inert gas, nitrogen helps maintain a stable carbon skeleton structure and promotes uniform distribution of pores. In some embodiments, the volume ratio of CO2 to N2 is set to 3:7. This atmosphere ratio can effectively optimize the pore structure and reduce the negative impact of gas reactions during the carbonization process.
[0072] As an option, a small amount of oxygen can be further added to the atmosphere to accelerate the surface repair of the material with the participation of trace oxygen, making it more hydrophilic and wettable, thereby improving the cycle performance and stability of the battery. However, such atmosphere control requires very precise adjustment to ensure that the oxygen concentration is not too high, resulting in oxidation of the material.
[0073] By precisely controlling the porosity, the electrochemical performance of the negative electrode material can be significantly improved. When the porosity is controlled within the range of 55% to 65%, the specific surface area and ion conductivity of the material can be effectively guaranteed, thereby optimizing the performance of the battery. Higher porosity helps to increase the specific capacity because the larger specific surface area provides more lithium ion reaction interfaces, thereby increasing the overall capacity of the battery.
[0074] Specifically, controlling the porosity not only increases the specific surface area of the material, but also optimizes the distribution of pore size, allowing the material to adapt to faster ion diffusion and reduce the resistance to ion diffusion. During high-rate discharge, the optimized pore structure can reduce the internal resistance of the material, allowing the battery to achieve higher power output in a short period of time.
[0075] Through the fine control of porosity, the cyclic stability of the material has also been significantly improved. A more uniform and moderate pore structure helps to slow down the expansion and contraction of the material during multiple charge and discharge processes, thereby increasing the service life of the battery. In some embodiments, by optimizing the porosity, the resulting negative electrode material can maintain a higher specific capacity and lower capacity decay over more than 1,000 charge and discharge cycles.
[0076] Through precise control of porosity, the obtained porous carbon negative electrode material shows obvious improvement in electrochemical performance.
[0077] In some embodiments, by adjusting the porosity and pore size distribution, the material not only has higher battery performance, but also exhibits good mechanical stability and low internal resistance in practical applications. The successful implementation of this process ensures that the porous carbon-coated modified negative electrode material has a long cycle life and high energy density, making it an ideal choice for high-performance lithium-ion battery negative electrode materials.
[0078] S4's porosity control method not only optimizes the pore structure of the material, but also improves the battery's specific capacity, rate performance and cycle stability, providing strong technical support for the widespread application of the final negative electrode material in lithium-ion batteries.
[0079] S5, protective coating deposition: forming an interfacial stabilization layer on the surface of the carbon material to improve the stability and conductivity of the negative electrode material; S5 deposits a protective coating to enhance the performance of the material in high-rate charge and discharge and long-term use. The deposition of the protective coating can not only effectively reduce the side reactions between the electrolyte and the surface of the negative electrode material, but also improve the mechanical strength, thermal stability and conductivity of the electrode material, thereby significantly improving the overall performance and service life of the battery.
[0080] In this embodiment, a sol-gel method is used to deposit titanium dioxide (TiO2) as a protective coating. The sol-gel method can form a uniform and dense coating to ensure that the surface of the negative electrode material is uniformly protected. Specifically, 0.8 to 1.5 parts of TiO2 are first mixed with 0.5 to 2.0 parts of titanium tetrachloride (TiCl4), and the volume ratio of TiCl4 to ethanol is set to 1:50. This ratio can ensure that the TiCl4 in the solution can completely react with ethanol to form a uniform TiO2 solution. Through the sol-gel method, the TiO2 coating can be uniformly deposited on the surface of the carbon skeleton and form a thin and dense protective layer. The protective coating deposition also includes: depositing MoS2 by CVD method, using MoO3 and sulfur powder as precursors, and placing them in different temperature zones, wherein the MoO3 temperature is 750°C and the S temperature is 200°C; using Ar / N2 mixed atmosphere, the volume ratio is 3:7, and the reaction time is 20-40min; after the reaction, it is naturally cooled to form a stable MoS2 coating.
[0081] Generally, the solution needs to be stirred for about 2 hours to ensure that TiCl4 and ethanol react fully. Through this process, TiCl4 is hydrolyzed in the solution and then polymerized to form a TiO2 precursor sol. At this point, the particles of the TiO2 precursor are evenly distributed, forming a transparent solution suitable for the subsequent deposition process.
[0082] As an option, during the deposition process, the permeability of the solution is further improved by suspending the negative electrode material in the TiO2 solution and using ultrasonic assisted deposition technology. The ultrasonic frequency used in this process is 20kHz, the power is 150W, and the reaction time is 4 to 6 hours. Ultrasonic vibration can promote the uniform distribution of the solution, effectively avoid uneven coating thickness, and improve the fluidity and permeability of the TiO2 solution, ensuring that the solution evenly covers the entire carbon skeleton surface and enters its pore structure.
[0083] Specifically, through the action of ultrasound, TiO2 particles can be more evenly distributed and less likely to agglomerate, thus ensuring the consistency of the coating thickness. The high-frequency vibration of ultrasound allows the TiO2 solution to fully penetrate the micropores of the material, allowing the coating to be evenly deposited inside the pores, which plays an important role in improving the conductivity, stability and long-term stability of the negative electrode material.
[0084] After the deposition is completed, the sample needs to be cleaned to remove the residual TiO2 solution. Then, the deposited material is calcined at 400°C, and the calcination time is controlled between 30 minutes and 60 minutes. The purpose of calcination is to remove the solvent and organic components in the TiO2 precursor and further promote the conversion of TiO2 into a crystalline state. Through calcination, the TiO2 coating can become dense and stable, improve its compatibility with the electrolyte, thereby reducing the side reactions between the electrolyte and the carbon material and extending the service life of the battery.
[0085] The main advantage of the sol-gel method for depositing TiO2 coatings is that it can achieve more uniform coating deposition at lower temperatures, while effectively controlling the thickness and morphology of the coating. Titanium dioxide (TiO2) as a protective coating has good chemical stability, thermal stability and extremely high electrochemical stability, which can significantly improve the conductivity of the negative electrode material, prevent unnecessary side reactions between the carbon skeleton and the electrolyte, and optimize battery performance.
[0086] As an option, the thickness of the TiO2 coating is usually controlled between 3nm and 8nm. A thinner coating helps maintain a low internal resistance of the battery while providing adequate protection to reduce the reaction between the electrolyte and the surface of the negative electrode material. If the coating is too thick, it may lead to a decrease in the conduction efficiency of electrons and ions, affecting the rate performance of the battery.
[0087] In some embodiments, the TiO2 coating can effectively enhance the surface stability of the material, reduce the structural changes caused by long-term battery charging and discharging, and improve the cycle stability of the battery. Through the calcination process, the crystal structure of TiO2 is further optimized, which improves the mechanical strength and stability of the coating and avoids the degradation of the coating at high temperature or high current density.
[0088] The thickness of the protective coating has a significant effect on the electrochemical performance of the negative electrode material. As an option, the coating thickness is usually set in the range of 3 to 8 nm to balance electronic conductivity and ion diffusivity. A thicker TiO2 coating can effectively protect the carbon skeleton and reduce the side reactions between the electrolyte and the surface of the carbon material, but an overly thick coating may hinder the conduction of electrons and ions, thereby affecting the rate performance of the material.
[0089] Specifically, the role of TiO2 coating is not only a physical barrier, but more importantly, it can improve the compatibility of electrolyte and electrode surface through chemical reaction. This can reduce the corrosion of soluble chemical components in the electrolyte to the electrode and prevent the electrolyte from reacting with the negative electrode material. Especially in high current density and high temperature environment, the coating can ensure the stability of the battery.
[0090] Through the deposition of the protective coating, the resulting negative electrode material shows a significant improvement in electrochemical performance. Specifically, the TiO2 coating can significantly improve the conductivity of the material, allowing the negative electrode material to better conduct electrons. During long-term charge and discharge cycles, the TiO2 layer effectively reduces the corrosion of the electrolyte on the carbon skeleton and enhances the cycle stability of the battery.
[0091] In some embodiments, by depositing a TiO2 coating, the resulting negative electrode material exhibits lower internal resistance during high-rate discharge and exhibits less capacity decay during long-term use. The stability of the coating enables the negative electrode material to maintain a good specific capacity at a higher current density, thereby improving the power density and energy density of the battery.
[0092] The deposition of TiO2 protective coating not only effectively improves the conductivity and chemical stability of the negative electrode material, but also greatly enhances its compatibility with the electrolyte. The TiO2 coating significantly improves the battery's cycle life, rate performance and overall battery performance by improving chemical and electrochemical stability.
[0093] S6. Final heat treatment of negative electrode materials: Optimize the surface polarity and perform low-temperature sintering of negative electrode materials to improve mechanical stability and electrolyte wettability; S6 further improves the mechanical stability, electrical conductivity and interfacial compatibility of the material with the electrolyte through final heat treatment. This treatment process ensures the high efficiency and reliability of the material in high-rate charge and discharge and long-term cycle use. The implementation of the final heat treatment will ensure the long-term stability of the negative electrode material during battery use and optimize the overall performance of the battery.
[0094] In this embodiment, the final heat treatment includes two key processes: cold plasma treatment and low temperature sintering. These two processes act on the surface polarity, structural stability and electrolyte affinity of the material respectively, and are key steps to improve the performance of the negative electrode material.
[0095] The first step is cold plasma treatment, which uses inert gases such as nitrogen or argon to generate plasma through ionization. The main purpose of cold plasma treatment is to introduce more polar functional groups, such as carboxyl (-COOH) and hydroxyl (-OH), on the surface of the material through physical and chemical effects. These polar functional groups significantly increase the affinity between the material surface and the electrolyte molecules and enhance the wettability of the electrolyte, thereby reducing the side reactions between the electrolyte and the electrode material and improving the stability and cycle life of the battery.
[0096] Generally, the cold plasma treatment time is set for 5 to 15 minutes. During the treatment process, the plasma flow is evenly distributed on the surface of the material, ensuring that the surface of each particle is evenly treated to maximize the introduction of polar functional groups. In this way, the surface of the negative electrode material is significantly chemically activated, which can better adsorb ions in the electrolyte, especially under high-rate charge and discharge conditions, and can effectively improve the conductivity and ion mobility of the battery.
[0097] As an option, the gas for cold plasma treatment can be nitrogen, argon or oxygen, and the type and flow rate of the gas can be adjusted according to specific needs. Nitrogen and argon are usually used to generate inert plasma to optimize surface polarity, while oxygen helps to introduce oxygen functional groups on the surface, further improving the stability and wettability of the electrode surface.
[0098] Subsequently, low-temperature sintering is performed to further enhance the mechanical stability and structural integrity of the material. Low-temperature sintering is generally carried out in the temperature range of 500°C to 700°C, and the sintering time is controlled to be 20 minutes to 60 minutes. This temperature range can further optimize the internal structure of the material, avoid pore shrinkage caused by excessively high temperatures, and maintain good porosity and structural stability of the negative electrode material.
[0099] Specifically, low-temperature sintering helps eliminate stress that may be generated during high-temperature carbonization, while improving the strength and stability of the carbon skeleton. During the sintering process, the particles of the material will undergo moderate melting and bonding, promoting the compaction of the microstructure of the material and enhancing its overall strength and conductivity. By properly controlling the sintering temperature and time, the mechanical strength and electrochemical stability of the electrode material can be improved while ensuring the integrity of the pore structure.
[0100] Cold plasma treatment and low-temperature sintering, as common surface modification and heat treatment methods, have significant advantages in improving the surface polarity, wettability and mechanical stability of materials. Cold plasma treatment introduces functional groups such as oxygen, nitrogen and hydrogen through the chemical reaction between the free radicals in the plasma and the surface of the material. These functional groups can not only enhance the surface polarity of the material, but also effectively improve the compatibility of the material with the electrolyte, thereby reducing side reactions during battery use.
[0101] As an option, gas components such as nitrogen and argon in cold plasma treatment can generate some stable surface functional groups by inducing chemical reactions during the plasma treatment process. These functional groups can improve the affinity between the material and the electrolyte while reducing the corrosion of the electrode due to harmful substances in the electrolyte, thereby extending the cycle life of the battery.
[0102] The role of low-temperature sintering is to make the material structure more compact and stable by sintering the material at a controlled temperature. Low-temperature sintering can not only remove the residual stress in the material, but also effectively enhance the mechanical strength of the material, making the material more able to withstand thermal expansion and contraction during long-term charging and discharging. Through low-temperature sintering, the electrical conductivity of the material is improved, and the harmful substances that may be generated during the sintering process will also be effectively removed, thereby improving the long-term stability of the electrode.
[0103] Through the final heat treatment, the surface and internal structure of the negative electrode material are fully optimized. Cold plasma treatment can significantly improve the surface polarity of the material, increase its interfacial affinity with the electrolyte, and thus improve the wettability and stability of the battery. During high-rate charge and discharge, the optimized surface polarity helps to better adsorb electrolyte molecules, reduce side reactions between the electrolyte and the electrode surface, and ensure good performance of the battery at high rates.
[0104] Specifically, after cold plasma treatment, the polar functional groups introduced on the surface of the material significantly improve the compatibility of the electrolyte and the electrode, allowing the material to conduct electricity better during the charge and discharge process and reduce capacity decay caused by side reactions. Through low-temperature sintering, the mechanical stability of the negative electrode material is enhanced, avoiding changes in the material structure caused by thermal stress during the battery charge and discharge process, and maintaining the long-term stability of the material.
[0105] In some embodiments, the negative electrode material that has undergone the final heat treatment exhibits lower internal resistance and higher specific capacity during high-rate discharge and long-term cycle use. In particular, at high current density, the material can still maintain good performance and the capacity decay rate is significantly reduced.
[0106] Through the implementation of the final heat treatment step, the surface polarity, wettability and mechanical stability of the negative electrode material have been significantly improved. This treatment process not only optimizes the high-rate performance of the battery, but also significantly improves the long-term stability of the battery. Cold plasma treatment effectively improves the interfacial affinity between the electrolyte and the electrode by introducing surface functional groups, reduces side reactions, and extends the service life of the battery.
[0107] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A method for preparing a porous carbon-coated modified negative electrode material, characterized in that: The following steps are involved: S1. Low-temperature pre-carbonization: an organic framework structure is formed under the action of carbon source, nitrogen dopant, structure regulator and sacrificial template; S2. Etching to form a hierarchical pore structure: using a chemical etching method to remove the sacrificial template to form a carbon material skeleton with a specific pore distribution; S3, high temperature carbonization and structural reconstruction: high temperature carbonization is carried out in an inert atmosphere to crystallize the carbon material, and the pore distribution is optimized by atmosphere regulation; S4. Porosity control method of negative electrode materials: optimize pore distribution by controlling etching time and atmosphere to ensure the porosity and ion diffusion capacity of the material; S5, protective coating deposition: forming an interfacial stabilization layer on the surface of the carbon material to improve the stability and conductivity of the negative electrode material; S6. Final heat treatment of negative electrode materials: Optimize the surface polarity and perform low-temperature sintering of negative electrode materials to improve mechanical stability and electrolyte wettability.
2. The method for preparing a porous carbon-coated modified negative electrode material according to claim 1, characterized in that: The low temperature pre-carbonization comprises: Take 2.5-3.5 parts of phenolic resin as a carbon source, 0.5-1.2 parts of guanine as a nitrogen dopant, 0.2-0.6 parts of CTAB as a structure regulator, and add 1.0-2.0 parts of SiO2 as a sacrificial template, mix and stir in deionized water, the stirring time is 2.5-4.0 hours, and the stirring speed is 400-600rpm; The mixed solution is subjected to a hydrothermal reaction at a temperature of 160-180° C. for a duration of 10-14 h to form a gel precursor; Low temperature drying of the obtained precursor at 80-100°C for 12 h to remove the solvent; The initial carbonization is carried out at 500-600°C, the atmosphere is Ar / N2 mixed gas, and the carbonization time is 1.5-3.0h.
3. The method for preparing a porous carbon-coated modified negative electrode material according to claim 1, characterized in that: The etching to form the graded pore structure comprises: The low-temperature carbonized sample was etched using a 40-50% HF solution for 2.0-3.5 h. Etching was performed under the assistance of 40kHz, 100W ultrasound to improve the uniformity of the pore structure; After washing with deionized water until neutral, vacuum drying is performed at 80-100°C for 10-14h.
4. The method for preparing a porous carbon-coated modified negative electrode material according to claim 1, characterized in that: The high temperature carbonization and structural reconstruction include: The etched sample is heated to 800-900°C at 5-10°C / min in an inert atmosphere and kept at this temperature for 1.5-3.0h; During the cooling process, a CO2 / N2 atmosphere was introduced with a gas volume ratio of 3:7 to control the pore structure; After cooling, XRD analysis is performed to ensure that the crystallinity of the carbon material meets the expected requirements.
5. The method for preparing a porous carbon-coated modified negative electrode material according to claim 1, characterized in that: The porosity control method of the negative electrode material comprises: By controlling the etching time, the porosity of the obtained material is within the range of 55-65%; The fractal Brownian motion model is used to optimize the pore size distribution so that the Hurst index is between 0.7 and 0.85; The Levy flight diffusion model was used to optimize the mesopore ratio and control the Levy index α at 1.
5.
6. The method for preparing a porous carbon-coated modified negative electrode material according to claim 1, characterized in that: The protective coating deposition comprises: 0.8-1.5 parts of TiO2 were deposited by sol-gel method, with 0.5-2.0 parts of TiCl4 as precursor, the volume ratio of TiCl4 to ethanol was 1:50, and the stirring time was 2h; The negative electrode material is suspended in a TiO2 solution and subjected to ultrasound-assisted deposition with an ultrasound frequency of 20kHz, a power of 150W, and a reaction time of 4-6h; After being taken out, it is dried and calcined at 400°C for 30-60 minutes.
7. The method for preparing a porous carbon-coated modified negative electrode material according to claim 6, characterized in that: The thickness of the TiO2 protective layer is controlled at 3-8 nm to ensure the balance of electron-ion transmission.
8. The method for preparing a porous carbon-coated modified negative electrode material according to claim 7, characterized in that: The protective coating deposition further comprises: 0.6-1.2 parts of MoS2 were deposited by CVD method, with 1-5 parts of MoO3 and 2-8 parts of sulfur powder as precursors, and placed in different temperature zones, where the temperature of MoO3 was 750℃ and the temperature of S was 200℃; Use Ar / N2 mixed atmosphere, volume ratio 3:7, reaction time 20-40min; After the reaction, it is cooled naturally to form a stable MoS2 coating layer.
9. The method for preparing a porous carbon-coated modified negative electrode material according to claim 1, characterized in that: The final heat treatment of the negative electrode material comprises: After high-temperature carbonization, cold plasma treatment is used to optimize the polar groups on the material surface and improve its wettability with the electrolyte; Low-temperature sintering technology is used, with a temperature range of 500-700°C and a sintering time controlled at 20-60 minutes to enhance the mechanical stability of the electrode.
10. The method for preparing a porous carbon-coated modified negative electrode material according to claim 1, characterized in that: The thickness of the obtained porous carbon-coated modified negative electrode material is controlled at 5-20µm, and by adjusting the thickness of the protective layer, its specific capacity is ensured to be in the range of 1000-1200mAh / g.
Citation Information
Cited By
Preparation method of porous carbon-silicon composite negative electrode material of lithium battery and lithium battery
CN120432517A
Negative electrode active material, preparation method thereof and sodium ion battery
CN120527377A